Verifikasi Metode Pengujian Kadar Nitrit dalam Air Limbah Secara Spektrofotometri UV-Visibel: Verification of a UV-Visible Spectrophotometry Method for Analysis of Nitrite Levels in Wastewater - Imas Solihat; Ardina Purnama Tirta; Agung Pratama Ramdani; Achmad Nandang Roziafanto (KOVALEN: Jurnal Riset Kimia, 2022)
Wastewater is the residue from a business and or activity in the form of liquid. One of the chemical compounds that cause pollution is nitrite. The nitrite level in wastewater is a key parameter in determining water quality because of its toxicity. The standard method for nitrite analysis refers to SNI 06-6989.9-2004 using sulfanilic acid and N-(1-naphthyl)-ethylenediamine dihydrochloride (NED) reagents. Linearity, instrument detection limit (LDI) and quantification detection limit (LOQ), precision, accuracy, and calculation of measurement uncertainty estimation are some of the verification parameters that were tested. The regression curve's results showed that the correlation value (r) = 0.9998, the instrument detection limit value of 0.0014 mg/L, the quantitation limit value of 0.0035 mg/L, the precision value (%SBR) of 1.30 percent, the accuracy value is in the range (90-100)% and the relative uncertainty of 5.88 %. The verification results suggested that the UV-Visible spectrophotometer-based nitrite test technique in wastewater had passed the acceptance requirements and may be utilized for routine laboratory analysis.